Organisasi Atau Perusahaan Mengenali Aset Intelektual Teknologi Untuk Berbagi Informasi Menggunakan Sumber Daya Manusia Dan Pengetahuan - Hesti Kusumaningrum; Adinda Rahmania Asti; Aesha Najwa Alia (STIKes Ibnu Sina Ajibarang, 2024)
In this chapter, we also discuss how human capital can be utilized in an organization. We show the important role of social and technological capital and how it can be attracted, developed, and maintained. We also discuss the role of technology in leveraging human resources. By discussing relatively simple means of using technology, such as email and networks where individuals can collaborate via personal computers. We also discuss more advanced uses of technology, for example advanced Management Systems. In the final section we also discussed the increasing importance of protecting a company's intellectual property.